2017
DOI: 10.1002/clc.22763
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and design of the Drug‐Eluting Stents vs Bare‐Metal Stents in Saphenous Vein Graft Angioplasty (DIVA) Trial

Abstract: VA Cooperative Studies Program #571 (DIVA) was designed to evaluate the efficacy of drugeluting stents (DES) for reducing aortocoronary saphenous vein bypass graft (SVG) failure when compared with bare-metal stents (BMS) in participants undergoing stenting of de novo SVG lesions. Participants undergoing clinically indicated stenting of de novo SVG lesions were randomized in a 1:1 ratio to DES or BMS. Randomization was stratified by presence/absence of diabetes mellitus and the number of target SVG lesions (1 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…We identified 6 RCTs with a pooled sample of 1582 patients; 1456 (92%) were male. There were 797 patients in the DES group and 785 in the BMS group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified 6 RCTs with a pooled sample of 1582 patients; 1456 (92%) were male. There were 797 patients in the DES group and 785 in the BMS group.…”
Section: Resultsmentioning
confidence: 99%
“…Third, the samples of patients enrolled in the previous trials were small in size (3 trials had ≤80 patients), with only 2 trials enrolling relatively larger number of patients (DIVA enrolled 599 and analyzed 597; Is Drug‐Eluting Stenting Associated With improved Results in Coronary Artery Bypass Grafts? [ISAR‐CABG] enrolled 610) . Fourth, different trials reported variable embolic protective device utilization (ISAR‐CABG <5% and DIVA >65%) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since then, several RCTs have shown that DESs decrease the risk of target vessel revascularization (TVR) without affecting mortality . However, the most recently reported DIVA (DESs vs. BMSs in Saphenous Vein Graft Angioplasty) trial showed that DESs may not improve TVR in SVG compared to BMSs . Therefore, we conducted an updated comprehensive meta‐analysis of RCTs comparing DESs versus BMSs for SVG interventions using the largest sample size to date.…”
Section: Introductionmentioning
confidence: 99%